Endemic hepatitis E in the Czech Republic - Chalupa, Pavel; Vasickova, Petra; Pavlik, Ivo; Holub, Michal (Clinical infectious diseases, 2014)
BACKGROUND: An increasing incidence of endemic hepatitis E (HE) has been reported in developed countries. Thus, an evaluation of the clinical characteristics of the disease and the utility of the current diagnostic methods is warranted. METHODS: Fifty-one adult acute patients with HE hospitalized in a single center between the years 2009 and 2012 were evaluated. Serological and molecular techniques (detection of hepatitis E virus [HEV] RNA from stool and serum samples by quantitative reverse transcription polymerase chain reaction) with sequencing and phylogenetic analysis were used for diagnosis, and the clinical, laboratory, and epidemiological parameters of the patients were evaluated. RESULTS: Forty-nine (96.1%) patients had acute endemic HE and 2 (3.9%) had an imported infection. In the cohort of patients with acute symptomatic HE (n = 47), men outnumbered women (40:7), the patients were in older middle age (mean, 60.57 years), and they had elevated median values of total bilirubin (6.67 mg/dL), alanine aminotransferase (2288.82 U/L), aspartate aminotransferase (1251.76 U/L), gamma-glutamyl transferase (360.53 U/L), and alkaline phosphatase (197.06 U/L). Serology was positive in 50 (98%) of the patients, and 1 case was diagnosed by polymerase chain reaction only. HEV RNA was detected in at least 1 specimen from 84.3% of the patients, and 28 of 29 tested isolates belonged to genotype 3. The eating of meat, innards, other home-prepared pork products, or the tasting of raw meat before cooking were the most frequently reported data (reported by 25 patients [49.0%]). CONCLUSIONS: Large numbers of the endemic cases of HE were caused by HEV genotype 3, and the clinical characteristics of endemic HE were demonstrated.
Keywords: dospělí; Immunoglobulin G; Endemic Diseases; Humans; endemické nemoci; lidé středního věku; Middle Aged; Genotype; feces; Sequence Analysis, DNA; RNA virová; Czech Republic; hepatitida - protilátky; hepatitida E; endemic cases; incidence; virus hepatitidy E; mužské pohlaví; Česká republika; RNA, Viral; Serum; Feces; Adult; zoonosis; Hepatitis Antibodies; clinical findings; imunoglobulin G; Hepatitis E virus; ženské pohlaví; sekvenční analýza DNA; sérum; genotyp; lidé; imunoenzymatické techniky; Incidence; Aged; hepatitis E; senioři; Male; Hepatitis E; Immunoenzyme Techniques; Female